2005
DOI: 10.1051/gse:2005016
|View full text |Cite
|
Sign up to set email alerts
|

A region on chicken chromosome 2 affects both egg white thinning and egg weight

Abstract: We describe the results from genetic dissection of a QTL region on chicken chromosome 2, shown to affect egg weight and quality in an earlier genome scan of an F2 intercross between two divergent egg layer lines. As the 90% confidence intervals for the detected QTL covered tens of centiMorgans, new analyses were needed. The datasets were reanalysed with denser marker intervals to characterise the QTL region. Analysis of a candidate gene from the original QTL region, vimentin, did not support its role in contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 9 publications
0
16
1
3
Order By: Relevance
“…Previous study indicated that QTL regions on chromosomes 2, 4 and 8 might influence egg white thinning 25. A recent study suggested that QTL region on chromosome 2 affects both egg white thinning and egg weight 26.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study indicated that QTL regions on chromosomes 2, 4 and 8 might influence egg white thinning 25. A recent study suggested that QTL region on chromosome 2 affects both egg white thinning and egg weight 26.…”
Section: Discussionmentioning
confidence: 99%
“…; Honkatukia et al . ; Schreiweis et al . ) identified, QTL were rarely replicated and had wide confidence intervals for position.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these QTL have significant effects on these traits. For egg-related traits, approximately 50 QTL exercising the main effect have been reported, and no epistatic QTL have been discovered (Tuiskula-Haavisto et al 2002Kerje et al 2003;Wardecka et al 2003;Sasaki et al 2004;Hansen et al 2005;Honkatukia et al 2005;Schreiweis et al 2006;Wright et al 2006). For egg-related traits, approximately 50 QTL exercising the main effect have been reported, and no epistatic QTL have been discovered (Tuiskula-Haavisto et al 2002Kerje et al 2003;Wardecka et al 2003;Sasaki et al 2004;Hansen et al 2005;Honkatukia et al 2005;Schreiweis et al 2006;Wright et al 2006).…”
Section: Introductionmentioning
confidence: 99%